Principal’s Supervision in Improving Teacher’s Performance - Gusmiyati, Gusmiyati; Lian, Bukman; Fitria, Happy (Journal of Social Work and Science Education, 2021)
This study determined the supervision of school principals and teacher performance. This research was conducted in 18 Public Elementary Schools in Gelumbang. The research method used in this study was qualitative method with a descriptive approach. Data were collectied using interviews, observation, documentation, questionnaires, and literature review. The results of the study stated that the supervision process was carried out by the principal through several stages, namely 1) planning the supervision activities; 2) implementation of supervision; 3) feedback the results of supervision; 4) follow up on supervision results. Based on the results of the supervision before the follow-up, it was found that more than 50% of the 18 Elementary School teachers in Gelumbang were not yet both categories in preparing the administration of learning devices. After giving feedback and the results of the teacher supervision follow-up assessment conducted by the school principal, 40% of teachers in the excellent category and 60% of teachers in the quite good category, thus the results of the supervision can improve the performance of teachers in SD Negeri 18 Gelumbang. The paper contributes to more give attention of supervision, and the the teacher’s performance will be improved.